2023
DOI: 10.1038/s41467-023-38310-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the electronic structure through charge redistribution in dense single-atom catalysts for enhanced alkene epoxidation

Abstract: Inter-site interaction in densely populated single-atom catalysts has been demonstrated to have a crucial role in regulating the electronic structure of metal atoms, and consequently their catalytic performances. We herein report a general and facile strategy for the synthesis of several densely populated single-atom catalysts. Taking cobalt as an example, we further produce a series of Co single-atom catalysts with varying loadings to investigate the influence of density on regulating the electronic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…To validate the discussion, we take the Co/N–C SAC as an example to illustrate the energy level changes in the central Co atom. , As presented in Figure , the energy level of the Dirac point at the PZC sits marginally above the Fermi level. The Co atom exhibits spin polarization with one unpaired d xz electron, and the PZC lies at about −0.36 V vs SHE, aligning with previous studies …”
Section: Resultsmentioning
confidence: 99%
“…To validate the discussion, we take the Co/N–C SAC as an example to illustrate the energy level changes in the central Co atom. , As presented in Figure , the energy level of the Dirac point at the PZC sits marginally above the Fermi level. The Co atom exhibits spin polarization with one unpaired d xz electron, and the PZC lies at about −0.36 V vs SHE, aligning with previous studies …”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations revealed a positive correlation between electron transfer and intersite distance of SACs, where the emerged electron redistribution effect was continuously weakened as the distance elongated. Cao et al 59 prepared a series of Co SACs to understand the influence of single-atom density on the electronic structures. As the density of Co sites increased, the whole support became more chargeconnected, resulting in charge redistribution that in turn accumulated more charge on densely populated Co SACs.…”
Section: Spin Momentmentioning
confidence: 99%
“…In addition, Cao et al 59 revealed the electronic structure of the metal center in densely populated SACs. To correlate the single-atom density with metal loading, they prepared a series of Co SACs ranging from 5.4 to 21.2 wt % (Figure 9f).…”
Section: Coupling Reactionmentioning
confidence: 99%
See 2 more Smart Citations